Catalytic Disproportionation of Hydrazine Promoted by Biomimetic Diiron Complexes with Benzene‐1, 2‐Dithiolate Bridge Modified by Different Substituents. Issue 45 (19th November 2020) - Sun, Tie; Xu, Sunlin; Yang, Dawei; Su, Linan; Wang, Baomin; Qu, Jingping
Abstract : A series of thiolate‐bridged diiron nitrogenase mimics featuring benzene‐1, 2‐dithiolate (bdt) ligand modified by different substituents were synthesized and characterized by X‐ray crystallography. Electrochemical studies by cyclic voltammetry demonstrate the redox potentials of these complexes depend on the electron‐withdrawing or electron‐donating nature of different substituents. Importantly, all these complexes can serve as catalysts for disproportionation of hydrazine to ammonia and dinitrogen, wherein the complex with the most negative reduction potential induced by strong electron‐donating NMe2 group exhibits the best catalytic activity. This result bodes well for efficient catalyst design for N–N bond cleavage of hydrazine. In addition, a well‐defined diiron diazene complex can be independently synthesized and also catalyze the hydrazine disproportionation to ammonia. However, relatively low yield suggests this species may not be a key intermediate during the catalytic cycle, unlike the other reported bimetallic systems. Abstract : The substituent modulation of the redox non‐innocent benzene‐1, 2‐dithiolate ligand has an obvious effect on the catalytic activity of hydrazine disproportionation to ammonia promoted by biomimetic diiron nitrogenase model complexes with different reduction potentials.